Synthesis, characterisation and evaluation of ferrocene-containing Novobiocin analogues for anticancer and antiplasmodial activity through inhibition of Hsp90 - Mbaba, Mziyanda (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
Novobiocin (Nb) is a coumarin type antibiotic isolated from the bacterium species of Streptomyces and possesses modest anticancer and antimalarial activities. Nb and analogues have been extensively explored as potential anticancer agents through inhibition of the C- terminal domain of heat shock protein 90 (Hsp90), which plays a pivotal role in the proteinfolding machinery of cells. There has been little effort in the exploration of Nb and derivatives for antimalarial activity. Incorporation of organometallic units, such as ferrocene (Fc), into bioactive chemical scaffolds remains an attractive approach for developing new therapeutic agents for treatment of several ailments. The current study sought to investigate the anticancer and antiplasmodial effects of incorporating ferrocene (Fc) into Nb scaffold presumably through inhibition of Hsp90. The ferrocenyl Nb analogues containing simplified structural motifs such as phenyl, benzyl, and piperidine were synthesized in six to nine steps employing conventional synthetic organic protocols adapted from literature, and the compounds were accessed in reasonable yields. For comparison purposes, a selection of organic Nb analogues were also included in the study. The target compounds were characterized by spectroscopic techniques including 1-dimensional nuclear magnetic resonance (1D NMR) and high-resolution mass spectroscopy. The synthesized compounds were evaluated in vitro for potential anticancer and antiplasmodial activities using the breast cancer cell line (HCC38) and chloroquine-sensitive strain (3D7) of the malaria parasite, Plasmodium falciparum. The presence of the Fc unit was found to enhance both anticancer and antiplasmodial activities of the resultant ferrocenyl Nb compounds with IC50 values in the low to mid micromolar range. Hsp90 inhibitory studies of the ferrocenyl Nb analogues possessing superior activities (2.13a and 2.20c) were also conducted using different yeast strains expressing both human and malarial Hsp90 isoforms: hHsp90a/p and PfHsp90, respectively. The results of Hsp90 inhibitory studies suggested no direct correlation between the observed activities of the analogues and Hsp90 inhibition. However, since the conditions of the assay were not optimised due to time constrains of the project, these observed data remained to be confirmed.
Keywords: Antibiotics -- Synthesis; Ferrocene; Heat shock proteins; Antimalarials; Cancer --Chemotherapy